UNDERSTANDING AND DEVELOPING LITERACY IN THE ESL/EFL CLASSROOM - Marietta S. Rossetto; Mirella Wyra (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2014)
Abstract: Literacy in the Australian Curriculum is defined in terms of the important role language plays in the construction of meaning in diverse social and cultural contexts and their related situations (ACARA 2013, Halliday & Hasan,1985; Vygotsky,1976). To this end, in this paper we will briefly review some relevant pathways to literacy, namely, the teaching/and learning cycle that informs the literacy pedagogy, and the language learning theories that underpin the accepted literacy approach choices. In addition, this paper will address an important link to literacy, namely, the intercultural understanding general capability. This will be done via a brief coverage of the work of Golding (2005) in relation to his suggestions regarding the development of ‘a thinking classroom’. This will be achieved in an arena that also presents the views of other researchers (Pohl, 2000; Pope & Denicolo, 2001; Arthur, 2005; Lipson, 2006) who also believe in the importance of student and teacher wellbeing in the classroom. It is hoped that the discussions that are covered in this paper will provide a useful review of the relevant literature and related findings. Keywords:literacy, intercultural understanding, text types, genre theory